ASSESSING RISK MANAGEMENT IN SHARIA BANKING - Yahya, M.; Saparuddin, Saparuddin; Siregar, Siregar; Sugianto, Sugianto (CV. Radja Publika, 2022)
Risk management is an important element whose application is very important, especially in Bank as one of financial institution. In the circumstances of the external and internal environments of the rapidly expanding banking, Islamic banks are always faced with various types of risk with varying levels of complexity and inherent in their business activities.s